Judging ‘Close Family Relations’ in Irregular Migration: The Production of Legal, National and Familial Orders in Finnish Courts - Taina Cooke (Nordic Journal of Migration Research, 2022)
This article examines the ways in which Finnish courts co-construct families and the legality of immigration in their decisions over the facilitation of ‘illegal immigration’. Building on scholarship that stresses the central role of migrant social networks and family ties in cross-border mobility, it challenges the placing of transnational organised crime at the centre of debates concerning irregular migration. Analysing how the Finnish courts engage with hegemonic family ideals and the notion of lived family relations in their decisions, this study aims to reveal the shifting criteria that appears in the background of the courts’ decision-making yet highlights an overall receptive approach to diverse facilitator–traveller family ties demonstrated by different judges. The conclusion reached is that Finnish judges are prepared to push the boundaries of what is legal in the context of irregular migration and challenge the ‘national order of things’ in order to account for motives that relate to family ties between the facilitators and the travellers. In the climate of increased regulation of cross-border mobility, highlighting the law courts’ receptive approach to diverse facilitator–traveller family ties reveals a more complex role of the state in managing migration and challenges the prominence of the migration-security nexus.